The view of the members of accountancy profession on ethical behavior and the effect of tax payers on displaying ethical behavior: A qualitative and quantitative research on a local scale in Turkey - (:unkn) unknown (International Economic Society, 2013)
In terms of accountancy, it has become very important that such procedures as the recording, categorization and reporting of financial operations of businesses are realized realistically within globalization, intensive competition and increasing transaction intensity. The business and transactions realized by the members of accountancy profession concern all parts of society. The ethical deviations that arise during this business and transactions would affect all parts of society. There are numerous factors that cause ethical deviations. One of these factors is the pressure formed by taxpayers on profession members. The study was carried out in Sivas city center in Turkey. The reasons why this city was selected for the research are because the population density is high and because it is a developing city in terms of production and government grants. The study was carried out on those Public Accountants and Certified Public Accountants operating in this city. The direction of the effect of taxpayers on the profession members when displaying ethical behavior and furthermore the view of profession members on ethical behavior were measured in the study. It was tried to find out whether there was a difference on displaying ethical behavior between those stating that there is a positive effect of taxpayers on the profession members when displaying ethical behavior and those that state there is no positive effect. © International Economic Society.
Keywords: Ethical deviation; Ethics; Occupational ethics; Occupational ethics approach